Body mass index as a predictor of mortality in bronchiectasis: A nationwide population-based study. (April 2021) - Lee, Jung Mo; Lee, Sang Ah; Han, Chang Hoon; Lee, Sun Min; Kim, Cheong Ju; Lee, Sang Chul; Park, Seon Cheol
Abstract: Introduction: The prognosis of bronchiectasis is not well known. The purpose of this study was to evaluate the association between body mass index (BMI) and mortality in bronchiectasis using a large nationwide population-based cohort. Material and methods: Using the National Health Insurance Service-Health Screening Cohort in Korea, individuals with bronchiectasis were identified from 2004 to 2006 and monitored for up to 10 years. Mortality in bronchiectasis was analyzed based on a BMI score <18.5 kg/m 2 (underweight), 1.85–22.9 kg/m 2 (normal weight), 23.0–24.9 kg/m 2 (overweight), and >25.0 kg/m 2 (obese). Results: A total of 2769 individuals with bronchiectasis were included. The underweight, normal weight, overweight, and obese accounted for 5.1%, 40.4%, 25.4%, and 29.3% of all patients with bronchiectasis, respectively. Compared to normal weight, underweight in bronchiectasis was associated with increased all-cause mortality (hazard ratio [HR] = 2.60; 95% confidence interval [CI] = 1.92–3.54), while obese was associated with decreased all-cause mortality (HR = 0.71; 95% CI = 0.55–0.93). This relationship between BMI and mortality was more prominent in respiratory disease-related mortality. Conclusions: BMI is a predictor of mortality in bronchiectasis. Underweight is associated with increased mortality among individuals with bronchiectasis while obese is associated with decreased mortality. Highlights: Body mass index (BMI) is a predictor of mortality in bronchiectasis. Underweight is associated with increased mortality in bronchiectasis. This association is prominent in respiratory disease-related mortality.